Novel insights into the pathophysiology of varicocele and its association with reactive oxygen species and sperm DNA fragmentation - Cho, Chak-Lam (Asian J Androl, 2016)
Varicocele has been associated with reduced male reproductive potential. With the advances in biomolecular techniques, it has been possible to better understand the mechanisms involved in testicular damage provoked by varicocele. Current evidence suggests the central role of reactive oxygen species (ROS) and the resultant oxidative stress (OS) in the pathogenesis of varicocele-associated male subfertility although the mechanisms have not yet been fully described and it is likely to be multifactorial. Excessive ROS is associated with sperm DNA fragmentation, which may mediate the clinical manifestation of poor sperm function and fertilization outcome related to varicocele. Testing of ROS/OS and DNA fragmentation has the potential to provide additional diagnostic and prognostic information compared to conventional semen analysis and may guide therapeutic management strategies in individual patient.